Erysipelas in an atypical location - Wańczyk-Dręczewska, Beata; Owczarczyk-Saczonek, Agnieszka B.; Placek, Waldemar J. (Dermatology Review/Przegląd Dermatologiczny, 2020)
Erysipelas is an acute bacterial disease of the skin and subcutaneous tissue. Its most commonly caused by group A beta-haemolytic Streptococci. Factors predisposing to infection include: old age, chronic diseases and immunodeficiency. Erysipelas the most typically develops on lower limbs. Very rarely the lesions are located on the trunk or the genital area. The clinical course is characteristic and includes: sudden onset, high fever, chills, pain as well as swelling, redness and excessive heat of the skin. The article describes a case of a female patient with erysipelas located in the back with a history of chronic myeloid leukaemia. In the differential diagnosis, skin lesions in the course of leukaemia and carcinomatous erysipelas had to be taken into account. The atypical location of skin lesions may have been caused by impairment and dysregulation of the immune system, both secondary to leukaemia and the use of an immunosuppressive drug. In dermatological practice, less typical locations of the infection have to be considered. Early implementation of appropriate treatment allows achievement of therapeutic success and avoiding complications.